Guided bone regeneration in long-bone defect with a bilayer mineralized collagen membrane - Fuli Peng; Xuelei Zhang; Yilei Wang; Rui Zhao; Zhiwei Cao; Siyu Chen; Yunxuan Ruan; Jingjing Wu; Tianxi Song; Zhiye Qiu; Xiao Yang; Yi Zeng; et al. (Collagen and Leather, 2023)
Abstract Bone regeneration for large, critical-sized bone defects remains a clinical challenge nowadays. Guided bone regeneration (GBR) is a promising technique for the repair of multiple bone defects, which is widely used in oral and maxillofacial bone defects but is still unsatisfied in the treatment of long bone defects. Here, we successfully fabricated a bilayer mineralized collagen/collagen (MC/Col)-GBR membrane with excellent osteoinductive and barrier function by coating the MC particles prepared via in situ biomimetic mineralization process on one side of a sheet-like pure collagen layer. The aim of the present study was to investigate the physicochemical properties and biological functions of the MC/Col film, and to further evaluate its bone regeneration efficiency in large bone defect repair. Fourier-transform infrared spectra and X-ray diffraction patterns confirmed the presence of both hydroxyapatite and collagen phase in the MC/Col film, as well as the chemical interaction between them. stereo microscope, scanning electron microscopy and atomic force microscope showed the uniform distribution of MC particles in the MC/Col film, resulting in a rougher surface compared to the pure Col film. The quantitative analysis of surface contact angle, light transmittance and tensile strength demonstrated that the MC/Col film have better hydrophilicity, mechanical properties, light-barrier properties, respectively. In vitro macrophage co-culture experiments showed that the MC/Col film can effectively inhibit macrophage proliferation and fusion, reducing fibrous capsule formation. In vivo bone repair assessment of a rabbit critical segmental radial defect proved that the MC/Col film performed better than other groups in promoting bone repair and regeneration due to their unique dual osteoinductive/barrier function. These findings provided evidence that MC/Col film has a great clinical potential for effective bone defect repair. Graphic abstract